The Potential of Single-Cell Oils Derived From Filamentous Fungi as Alternative Feedstock Sources for Biodiesel Production - Mhlongo, Sizwe I.; Ezeokoli, Obinna T.; Roopnarain, Ashira; Ndaba, Busiswa; Sekoai, Patrick T.; Habimana, Olivier; Pohl, Carolina H. (Frontiers in Microbiology, 2021)
Microbial lipids, also known as single-cell oils (SCOs), are highly attractive feedstocks for biodiesel production due to their fast production rates, minimal labour requirements, independence from seasonal and climatic changes, and ease of scale-up for industrial processing. Among the SCO producers, the less explored filamentous fungi (molds) exhibit desirable features such as a repertoire of hydrolyzing enzymes and a unique pellet morphology that facilitates downstream harvesting. Although several oleaginous filamentous fungi have been identified and explored for SCO production, high production costs and technical difficulties still make the process less attractive compared to conventional lipid sources for biodiesel production. This review aims to highlight the ability of filamentous fungi to hydrolyze various organic wastes for SCO production and explore current strategies to enhance the efficiency and cost-effectiveness of the SCO production and recovery process. The review also highlights the mechanisms and components governing lipogenic pathways, which can inform the rational designs of processing conditions and metabolic engineering efforts for increasing the quality and accumulation of lipids in filamentous fungi. Furthermore, we describe other process integration strategies such as the co-production with hydrogen using advanced fermentation processes as a step towards a biorefinery process. These innovative approaches allow for integrating upstream and downstream processing units, thus resulting in an efficient and cost-effective method of simultaneous SCO production and utilization for biodiesel production.